Michelle,

john is in general correct, but i would approach this problem differently and teach my calc students the same:

y=42 * (126/((x+168)) ^2

y= 42*(126*(x+168)^-1)^2

let U= 126*(x+168)^-1

then dU/dx= 126*( -1*(x+168)^-2)*(1) > the (1) here is from the chain rule applied to x+168

and your original is now y=42*U^2

so dy/dx = 42*2*U^1*dU/dx >chain rule here thus the dU/dx

sub back in and dy/dx = 84(126/(x+168))*[-126/(x+168)^2)]=-1333584/(x+168)^3

jeez, that's not easy to type....

jerry